Spray-dried fucoidan microparticles for pulmonary delivery of antitubercular drugs. (19th May 2018) - Cunha, Ludmylla; Rosa da Costa, Ana M.; Lourenço, João P.; Buttini, Francesca; Grenha, Ana
Abstract: Pulmonary tuberculosis accounts for 80% of cases and the delivery of antitubercular drugs into the lungs allows targeting the infected organ and, possibly, reducing systemic drug toxicity. This work aimed at using fucoidan as matrix of inhalable microparticles that associate two first-line antitubercular drugs, for an application in pulmonary tuberculosis therapy. Fucoidan is composed of fucose and sulphated sugar residues, moieties described as being recognised by surface receptors of alveolar macrophages, which host mycobacteria. Inhalable fucoidan microparticles loaded with antitubercular drugs were successfully produced with high association efficiencies of either isoniazid (95%) or rifabutin (81%). The microparticles evidenced no cytotoxicity on lung epithelial cells (A549). However, rifabutin-loaded microparticles showed a certain degree of toxicity on macrophage-like cells (THP-1) at the highest tested concentration (1 mg/mL). Furthermore, microparticles showed favourable aerodynamic properties for deep lung delivery (MMAD 2.0–3.8 µm) and, thus, show potential for an application as inhalable tuberculosis therapy.